PERAN PESANTREN AS’ADIYAH SENGKANG DALAM MEMBANGUN MODERASI ISLAM DI TANAH BUGIS - Darlis, Darlis (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2016)
Strengthening moderate Islam in the Archipelago is necessary today. Tug of war between religious radicalism and religious liberalism is one of the reasons that underlies this idea. In the middle of this feud, pesantren is expected to play an important role in strengthening religious ideas which are in accordance with the culture of Archipelago that is full of mercy. In this paper, I explore the role of Pesantren of As’adiyah Sengkang in building a moderate Islam in Bugis land. This paper shows that this pesantren has built and developed a moderate Islam in South Sulawesi through two ways; first, a pesantren network and Bugis Muslim scholars as  graduates of As’adiyah pesantren , who have been scattered  throughout Sulawesi island; second, religious doctrines of As’adiyah which are coloured with Ahlussunnah wal jama’ah either in faith, Islamic law, Islamic mysticism or method of preaching that promotes the principles of moderation ( tawassuth ), tolerance ( tasamuh ) and equilibrium ( tawazun ).